2017
DOI: 10.1186/s12868-017-0383-y
|View full text |Cite
|
Sign up to set email alerts
|

Day2day: investigating daily variability of magnetic resonance imaging measures over half a year

Abstract: BackgroundMost studies of brain structure and function, and their relationships to cognitive ability, have relied on inter-individual variability in magnetic resonance (MR) images. Intra-individual variability is often ignored or implicitly assumed to be equivalent to the former. Testing this assumption empirically by collecting enough data on single individuals is cumbersome and costly. We collected a dataset of multiple MR sequences and behavioural covariates to quantify and characterize intra-individual var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 29 publications
(29 reference statements)
0
29
0
Order By: Relevance
“…3, Supplementary Figs S8, S9, and S11). Given the increasing availability of multi-session rs-fMRI from many different research groups (Zuo et al 2014;Holmes et al 2015;Poldrack et al 2015;Filevich et al 2017;Gordon, Laumann, Gilmore, Newbold, et al 2017c), it might be possible to add another layer to the hierarchical model to account for intersite variability, in addition to intra-subject and inter-subject variabilities. Furthermore, our experiments did not differentiate between rs-fMRI runs collected within the same session versus rs-fMRI runs collected from different sessions.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…3, Supplementary Figs S8, S9, and S11). Given the increasing availability of multi-session rs-fMRI from many different research groups (Zuo et al 2014;Holmes et al 2015;Poldrack et al 2015;Filevich et al 2017;Gordon, Laumann, Gilmore, Newbold, et al 2017c), it might be possible to add another layer to the hierarchical model to account for intersite variability, in addition to intra-subject and inter-subject variabilities. Furthermore, our experiments did not differentiate between rs-fMRI runs collected within the same session versus rs-fMRI runs collected from different sessions.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Although the MS-HBM approach did not account for inter-site variability, we demonstrated that model parameters estimated from one site can generalize to another site with a different acquisition protocol and scanner (Figures 3, S8, S9, S11). Given the increasing availability of multi-session rs-fMRI from many different research groups (Zuo et al, 2014;Holmes et al, 2015;Poldrack et al, 2015;Filevich et al, 2017;Gordon et al, 2017c), it might be possible to add another layer to the hierarchical model to account for inter-site variability, in addition to intra-subject and inter-subject variability. Furthermore, our experiments did not differentiate between rs-fMRI runs collected within the same session versus rs-fMRI runs collected from different sessions.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…We performed a retrospective analysis of data of HP collected from the Day2day daily variability study, 18 and an ongoing observational single-center cohort (EA1/163/12). Inclusion criteria were as follows: a minimum of 18 years of age and no presence of any neurologic/psychiatric disorders, contraindications for an MR imaging examination, or incidental MR imaging findings.…”
Section: Cohortmentioning
confidence: 99%